Laparoscopic Management of Unruptured Interstitial Ectopic Pregnancy - Nahar, Shamsun (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A 27 years old women para -1 had a complaint of dullache pain in right iliac fossa for 5 days with irregular spotting. Her previous menstrual cycle was normal but in last one month she had an irregular spotting. On examination she was normotensive. Hb% was 65%. there was no tenderness during per abdominal examination but tenderness during per vaginal examination on right side. Transvaginal ultrasonography (TUVS) detected a degenerative sub serous fibroid of 3.5 x 3 cm on the right fundoanterior side, both adnexae were normal, no fluid was present in cul-de-sac. Her pregnancy test was positive but signs and symptoms of pregnancy were absent. Operative plan was intervention by laparoscope. An unruptured interstitial ectopic pregnancy was found at the anterolateral wall of the fundus. Laparoscopic excision was done and the uterine wall sutured with 2/0 polyprolylin. Post operative outcome was good. DOI: 10.3329/jbcps.v26i3.4199 J Bangladesh Coll Phys Surg 2008; 26: 147-148